The Effect of Empowering Leadership On Individual Innovative Behavior Mediated By Work Group Cohesiveness And Individual Learning Orientation In Company Distributor of Fast Moving Consumer Goods - Averina Patoding, Agatha (Asian Journal of Social and Humanities, 2024)
The focus of the research aims to test the effect of empowering leadership, work group cohesion, individual learning orientation on individual innovative behavior. This study uses a quantitative approach where the minimum sample used is 150 respondents of PT. N employees collected through questionnaires. In sampling applied non-probability sampling using purposive sampling technique. This study was analyzed using Partial Least Square-SEM or called PLS-SEM. The results of the study indicate that empowering leadership has a positive and significant effect on work group cohesion. However, empowering leadership does not affect individual innovative behavior and individual learning orientation. In addition, work group cohesion has a positive and significant effect on individual innovative behavior and individual learning orientation. Individual learning orientation also affects individual innovative behavior. Meanwhile, work group cohesion mediates empowering leadership on individual innovative behavior. However, individual learning orientation does not mediate the influence of empowering leadership on individual innovative behavior. In addition, it was found that individual learning orientation mediates the influence of work group cohesion on individual innovative behavior.